Carrier based pulse width modulated two-level and three-level Z-source inverters for distributed energy resources - Sheik Fareed Muhammad Musthafa Roomi (2016)
Global electrical power demands has seen a dramatic spike recently. Along with demands, deterrents like the shortage in electricity, spikes in electricity price, and power quality problems force many utility customers to examine alternative means of power generation. One of the best alternatives that can improve the traditional power grid is the Distributed Energy Resources (DER). These are small-scale power generation sources with high quality and reliable electricity, and are usually located onsite. All types of distributed energy sources require specific energy regulators, which enables direct connections of the energy source to the utility. Usually high performance voltage and current source inverters are used for dc-ac conversion. However, these traditional inverters support only the voltage buck operation. Due to their narrow obtainable output voltage property, these inverters cannot be interfaced solely for exploiting energy from renewable sources. These drawbacks can be overcome by designing inverters with voltage buck and boost capabilities. The traditional rule to achieve the voltage buck-boost conversion is by employing a dc-dc boost converter as a front end to the dc-ac inverter. As this conversion involves two converters being connected in series, drawbacks like cost, control and two-stage energy conversion motivate the need to look for an alternative. Therefore, as a solution, the Z-Source inverter (ZSI) was introduced in 2002. ZSI consists of an impedance network and performs single-stage energy conversion. ZSI has been widely preferred in research fields including this research due to advantages like wider obtainable output voltage, higher reliability and higher efficiency. Medium/high power applications are trending towards incorporating multilevel inverters due to a better output waveform quality and low electromagnetic interference (EMI) while employing devices of smaller voltage rating. In recent years, multilevel inverters that can provide both voltage buck and voltage boost has been the focus for many research studies as it greatly reduces the need for additional dc-dc converters. Therefore, this research also focusses on the multilevel ZSI. Furthermore, the topological design and control schemes for multilevel ZSI’s are investigated. Three-level ZSI topology is configured with two X-shaped LC impedance networks and is merged with the existing NPC inverter topology. The neutral point is formed between the two Z-Source networks. Even though modified modulation methods for controlling the inverter operation have been proposed, this research proposes a new modulation scheme (Reference Disposition Level Shifted Pulse Width Modulation) for three-level ZSI, which provides flexibility for easier implementation with reasonable voltage boosting, low harmonic and less iv switching loss across semiconductor devices. As the two impedance networks are supplied by two isolated dc sources, any voltage variability will lead to unbalanced voltage boosting. The main challenge lies in inserting the shoot through without introducing volt-sec error to the three-phase inverter output. Therefore, the proposed topology is designed based on the afore-mentioned aspects. Dual Z-Source Network Neutral Point Clamped inverter are investigated for ideal and non-ideal conditions with the proposed modulation method as the control scheme. The mathematical analysis for the system is modeled through the simulation and is determined to support the analysis. The experimental setup is assembled and the results are compared to prove the potency of the proposed modulation scheme. In addition, a two-level inverter topology and its various modulation schemes, that produce the unique shoot through states has been investigated. In addition to the traditional active and zero states, this unique shoot through states provide the voltage boost capability for the inverter. The different modulation methods for controlling the inverter are compared. Maximum Boost Control method is chosen for this research given that it provides wide operating range with maximum voltage gain. As a part of DER application, Proton Exchange Membrane Fuel Cell (PEMFC) stack, which is operated at nominal pressure and temperature, is designed. The design provides the flexibility of controlling the fuel flow rate using a fuel flow regulator. The designed fuel cell stack is then integrated with the conventional and the ZSI energy converters. The performance of both the converters is investigated under sustained and variable fuel flow rate.